The Influence of Family Background, Psychology and Perceived University Support Towards Self-Employment Intention among Public University Students in Malaysia - Asmaul Husna, Haris Fadzilah; Wan Mohd Hirwani, Wan Hussin; Mohammad Naim, Ismail; Farha Zafira Agos, Lokman; Mohammad Mujaheed, Hassan; Muhamad Hafiz, Hassan (Auricle Global Society of Education and Research, 2023)
Purpose: The current economic situation with increasing unemployment among graduates is ever important. The government of Malaysia has been promoting the entrepreneurship education among university students to overcome this problem. However, for this program to be effective, it is pertinent to look at the demand side of this program, the student’s and their intentions towards being self-employed.